First record of Cladocroce (Porifera: Haplosclerida: Chalinidae) from the Eastern Pacific ocean with the description of Cladocroce reina sp. nov. - Aguilar-Camacho, Jose Maria; Carballo, Jose Luis (Zootaxa, 2010)
Chalinidae is a family of haplosclerid sponges with a delicate reticulated chaonosomal skeleton of uni-, pauci- or multispicular primary lines which are connected by unispicular secondary lines, and with an ectosomal skeleton, if present, formed by a regular hexagonal, unispicular, tangential reticulation (Weerdt 2002). Currently, the family harbors only five valid genera (Chalinula, Cladocroce, Dendrectilla, Dendroxea and Haliclona; Soest et al. 2008), although recent molecular studies suggest that a new rearrangement of the present classification is needed (Redmond et al. 2007). Cladocroce was described by Topsent (1892) from specimens collected in the Atlantic Ocean. The principal characteristic of this genus is the presence of multispicular fiber tracts with a rather dense subisotropic reticulation in between (Weerdt 2002). After that, 10 species have been described, most of them from deep waters and cold climates (Putchakarn et al. 2004). Only three species have been found living in shallow waters: C. aculeata Pulitzer-Finali, 1982 from the Great Barrier Reef, C. burapha Putchakarn et al., 2004 from the Gulf of Thailand, and C. tubulosa Pulitzer-Finali, 1993 from the port of Mombasa, in Kenya. Sponge taxonomy studies in the Mexican Pacific coast have been focused mainly on hadromerids, and particularly on boring sponges (Carballo et al. 2008), and the current knowledge of haplosclerids is very scarce (Cruz-Barraza & Carballo 2006). In this paper, a new species of Cladocroce is described and compared with the other species recorded worldwide. With this contribution the genus Cladocroce increases to 12 species.